Citotoxic effect of Physalis peruviana (capuli) in colon cancer and chronic myeloid leukemia - Zavala, David (2006)
Objective: To determine Physalis peruviana cytotoxic activity in the colo-205 (colon cancer) and K562 (chronic mieloid leukemia) cell lines. Design: Experimental study. Setting: San Marcos Major National University Pharmacology Department and Cayetano Heredia Peruvian University Sciences and Phylosophy Faculty laboratories. Materials: The lines colo-205, K562 and 3T3 cell lines, P. peruviana ethanolic leave and stem extracts, and 5-FU. Interventions: Colo-205, K562 and 3T3 (normal mouse fibroblasts) cell lines were exposed to P. peruviana ethanolic leave and stem extracts, and 5-FU was used as positive control. Main outcome measures: Physalis peruviana cytotoxic activity in the colo-205 and K562 cell lines. Results: The leaves and stems Physalis peruviana IC50 in μg/ml in the colo-205 and K562 cell lines was respectively 1,93 (r=-0,89 p<0,01) and 0,84 (r=-0,91 p<0,01) for colo-205, 2,42 (r=-0,98 p<0,005) and 2,1 (r=-0.98, p<0.005) for K562, and 2,67 (r=-0,98 p<0,005) and 4,59 (r=- 0,96 p<0,005) for 3T3. The 5-FU IC50 was 3,57 (r=-0,96 p<0,005), 15,95 (r=-0,97 p<0,025), and 0,51 (r=-0,88 p =0,01) for colo- 205, K562 and 3T3 respectively. The leaves and stems extracts and of 5-FU selectivity index were respectively 1,38, 5,46, 0,14 for colo-205 and 1,10, 2,18, 0,032 for K562. Conclusions: The P. peruviana leaves and steams ethanolic extracts were more cytotoxic than 5-FU in the colo-205 and K562 cell lines. Furthermore the P. peruviana cytotoxic effects were less than 5- FU for 3T3 cells.